Pengaruh Kecerdasan Emosional Terhadap Hasil Belajar Siswa Mata Pelajaran Bahasa Indonesia Kelas XII. 11 SMA Negeri 5 Palembang - Sari, Mira; Oktriyanti, Selvia; Laniar, Heti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The low student learning outcomes are because students sometimes have their own emotions in terms of understanding the place and teacher in the classroom during the learning process. Students' emotional intelligence can be said to vary from one student to another. A person's emotional intelligence, namely being able to realize and manage one's own emotions. The purpose of this study was to determine how the influence of emotional intelligence on student learning outcomes in Indonesian language subjects in class XII. 11 SMA Negeri 5 Palembang. The research method used is descriptive method because this research aims to describe the effect of emotional intelligence on student learning outcomes in Indonesian language subjects in class XII. 11 SMA Negeri 5 Palembang. The population in this study were all students of class XII. 11 totaling 30 people consisting of 16 female students and 14 male students. While the sample in this study was taken from the entire population of 30 people. Measuring instruments in research are usually called research instruments, which are tools used in collecting data. Data analysis in this study is descriptive. It is known that there is an influence of students' emotional intelligence on the learning outcomes of students in class XII.11 at SMA Negeri 5 Palembang by 70%. This shows that students' emotional intelligence affects learning outcomes as well. Every learner must have learning activities in the knowledge of Indonesian Language, the knowledge possessed depends on the student's emotional self. Each learner has different emotional intelligence in utilizing their emotions. If students are able to use their emotional intelligence well, then in learning they will be more responsible and disciplined, so that it will indirectly affect their learning outcomes.